IMPLEMENTATION OF LEARNING EXPERIENCES BASED ON SPIRITUAL GROWTH IN THE INDEPENDENT CURRICULUM TO IMPROVE LEARNING OUTCOMES IN MADRASAH - Muhammad Hasyim (STAI AL-HIDAYAT Lasem, 2025)
:The purpose of this research is to describe the efforts to enhance students' learning experiences based on spiritual growth within the independent curriculum at MI Negeri 2 Probolinggo. This research employs a qualitative approach with a case study design. The data collection techniques used are interviews with the Head of the Madrasah, the Curriculum Deputy, and two subject teachers, as well as documentation. Data analysis is conducted through three interactive steps: (1) data condensation; (2) data display; and (3) conclusion drawing and verification. Data validity is ensured through source triangulation.The research results indicate that P5, which includes self-potential development, self-empowerment, self-understanding, self-improvement, and students' social roles, is part of the spiritual growth process in the independent curriculum aimed at enhancing students' learning experiences tailored to their needs. The enhancement of learning experiences cannot be achieved through mere verbal exposure. Learning experiences are obtained through various learning activities as mentioned above. This implies that the subject matter functions more as a means rather than an end. The spiritual growth approach in this independent curriculum illustrates various activities that are not only based on religious values but also uphold the affective aspects that students should possess.